Caracterização da estrutura genética de populações residentes e migradoras da espécie Salminus brasiliensis da Bacia do rio Mogi-Guaçu - Rossini, Bruno César (2010)
Dourado (Salminus brasiliensis Cuvier, 1816) is an excellent migratory fish, possessing large body and wide distribution in South America, with presence in Paraná, Uruguay, Paraguay and La Plata River Basins (Argentina, Brazil, Uruguay and Paraguay), in drainage of Laguna dos Patos (Rio Grande do Sul state, Brazil) and the upper portion of the Mamoré and Chaparé River system (Bolivia). This fish is much appreciated in gastronomy and sport fishing. However, with increasing habitat degradation, overfishing and damming of rivers due to electric power generation, the fauna of these areas has suffered large impacts, and studies aimed at conservation are needed. In this approach, microsatellite markers have been used to assess the genetic structure of natural populations in order to provide data for management and conservation programs. Despite the microsatellite markers are extremely useful for many organisms including dourado, there are not species-specific loci described yet. Thus, in the present study we used heterologous loci, described for three species related to S. brasiliensis in eight populations of this fish (four residents and four migratory). Samples of 201 animals were collected in the Mogi-Guaçú River (Cachoeira de Emas, Pirassununga, SP) during the years 2007-2009, including reproductive periods (November-February) and non-reproductive (March-October). DNA was extracted using protocol phenol: chloroform: isoamyl alcohol. We tested 29 microsatellite loci, 16 were described for Salminus franciscanus, six for Brycon hilarii and seven for Brycon opalinus. Of this total, only ten loci (nine for S. franciscanus and one for B. opalinus) have demonstrated excellent amplification and high polymorphism, being used in population analysis of S. brasiliensis. Statistical analysis was performed in Genepop 4.0 (HWE, heterozygosity, linkage disequilibrium), FSTAT 2.9.3. (FST, genetic diversity and allelic richness, Fis), GenAlEx 6 (private alleles), Popgene 1.31. (distance and genetic identities), Micro-Checker (null alleles) and Structure 2.3.1. (assignment test and population differentiation). The number of alleles ranged from eight (Sfra18) to 48 (Sfra02), considering all populations together. The levels of observed heterozygosity ranged from 0,668 (RT- 07/2008) to 0,776 (MT-01/2009), and seven populations were out of the HWE at least for one locus. The values of Nei's distance and genetic identity varied, respectively, from 0,08 to 0,29 and 0,75 to 0,92. The data show that these populations have high intra-population genetic variability and low population differentiation between them. The FST values, together with the data of gene and genotypic differentiation and the analysis in the software Structure pointed to the existence of at least two populations outside the breeding period in the analysis. For populations sampled within the reproductive period no structure was identified. These results may help to better understand about the migratory behavior and their reproduction in the region of Cachoeira de Emas, contributing to management actions related to fisheries and conservation of this important migratory fish species.